HIV/AIDS EPIDEMIC IN A WESTERN BORDER MUNICIPALITY OF RIO GRANDE DO SUL, BRAZIL: EVOLUTION, HIV CASCADE OF CARE AND LETHALITY - Davoglio, Rosane Silvia (2020)
Objective: To analyze the characteristics and trends of HIV/AIDS epidemic in Uruguaiana/RS between 2005 and 2015 through indicators related to infection and the HIV cascade of care. Methods: Descriptive study performed with secondary data from Health Information Systems of the Ministry of Health. Historical sets of indicators related to detection of HIV/AIDS cases and deaths were developed, comparing with national and state data from 2005 to 2015. Also, the HIV cascades of care were elaborated for the municipality between 2013 and 2015. Results: AIDS detection rates of Uruguaiana were higher in comparison with the country and state, the same happened with the mortality and lethality indicators, which varied among 35.1 and 17.7 deaths/100 thousands of inhabitants and 6.5 and 2.7 deaths/100 inhabitants, respectively. The HIV cascades of care showed an increase in individuals diagnosed with HIV in the period (from 1,125 to 1,527). The main gap occurred between the "diagnosed" and "linked" categories, expanding over time (78%, 48% and 43.4% respectively). There was a low proportion of individuals in the "undetectable viral load" category in the three years, ranging from 32% to 22.9%. Conclusion: Indicators of detection, mortality and lethality due to HIV/AIDS are high in Uruguaiana, with an increase in the number of people diagnosed with HIV and decrease in their link with health services, suggesting the need for advances in strategies to attract and link people living with HIV/AIDS to the health care network.